EFFECT OF DIFFERENT ARTIFICAL FFEDS FORMULATED FROM LOCAL INGREDIENTS ON THE MEAT QUALITY OF INDIAN MAJOR CARPS - S. Sultana; A. Zahra; T. Sultana; K. A. Al- Ghanim; S. Mahboob (Journal of Animal and Plant Sciences, 2016)
The effect of three isoproteineous (35 % crude protein) feeds, prepared from different ingredients, on the meat quality of major carps (Catla catla, Cirrhinus mrigala and Labeo rohita) was investigated.   Total 90 fingerlings of each fish species were randomly stocked with three replicate tanks of each treatment. Maximumquantitative protein concentration was recorded in C. mrigala (0.798 + 0.013 mg/ml) followed by L. rohita (0.666 + 0.001 mg/ml) fed with diet B, whereas diet C showed maximum protein concentration (0.725 + 0.015 mg/ml) in C. catla.  Minimum protein concentration was recorded as (0.495 + 0.019, 0.567+ 0.003 and 0.564 + 0.036 mg/ml in C. mrigala, L. rohita and C. catla fed with diet A, respectively. The order of protein concentration in C. mrigala and L. rohita was diet A < C < B, whereas in C. catla it was diet A < B < C. The protein efficiency of diets A and B in C. mrigala and L. rohita were statistically different. In C. catla the protein efficiency of the diet A was significantly different (P<0.01) from diet B, and diet A exhibited non-significant (P>0.05) with diet C. The qualitative analysis depicted a maximum number of bands of isolated protein subunits in C. mrigala which were16, 13 and 15, respectively, in diets A, B and C. In L. rohita 13, 11 and 12 bands of isolated proteins of different molecular weight was observed after the effect of diet A, B and C, respectively. The number of bands of isolated protein subunits in L. rohita were 13, 11 and 12 in case of diets A, B and C. In C. catla 12, 10 and 11 in  bands of isolated proteins of different molecular weights were observed after feeding with A, B and C, respectively. The overall order of the number of bands of isolated protein subunits in all fish species was diet A > C > B.
Keywords: fish; growth rate; feed efficiency; SDS-PAGE